Study on Dynamic Characteristics of the Disc Spring System in Vibration Screen - Jiacheng Zhou; Chuzhe Zhang; Ziqiu Wang; Kuanmin Mao (Shock and Vibration)
To avoid too large exciting force in traditional linear vibrating screen and unstable working state in resonance screen, the disc spring system is applied in the linear vibration screen. The model of the disc spring system in vibration screen is established by simulation and experiment. The characteristics of modal and amplitude of the disc spring system in vibration screen are studied. We found that the disc spring system vibrates in vertical direction at the third-order natural frequency, which is consistent with the direction of the vibration screen when screening particles. Moreover, the third-order natural frequencies in simulation and experiment are basically consistent. Furthermore, the maximum amplitude of the disc spring system appears at 960 r/min (16 Hz), which is in accord with the third-order natural frequency. Meanwhile, the amplitude increases proportionally with the increase of exciting force, while the amplification factors are the same under three different exciting forces. This indicates that the disc spring system has excellent linearity. The results of research provide guidance for design and application of elastic components on the vibration screen.